2010
DOI: 10.1111/j.1743-6109.2010.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Priapus is Happier with Venus than with Bacchus

Abstract: Introduction The relationship between alcohol consumption and erectile function is still not completely clarified. Aim Aims of the present study are to explore a number of biological and clinical correlates of alcohol consumption in a sample of men consulting for sexual dysfunction, and to verify possible associations with the incidence of major adverse cardiovascular events (MACEs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
25
1
Order By: Relevance
“…Evidence from observational studies suggests a positive dose–response association between quantity and duration of smoking and the risk of erectile dysfunction 86,87 . Similar results have been documented for alcohol abuse 88 . In addition, diets that are low in whole-grain foods, legumes, vegetables and fruits, and high in red meat, full-fat dairy products, and sugary foods and beverages are all associated with an increased risk of erectile dysfunction 89 .…”
Section: Diagnosis Screening and Preventionsupporting
confidence: 89%
“…Evidence from observational studies suggests a positive dose–response association between quantity and duration of smoking and the risk of erectile dysfunction 86,87 . Similar results have been documented for alcohol abuse 88 . In addition, diets that are low in whole-grain foods, legumes, vegetables and fruits, and high in red meat, full-fat dairy products, and sugary foods and beverages are all associated with an increased risk of erectile dysfunction 89 .…”
Section: Diagnosis Screening and Preventionsupporting
confidence: 89%
“…Subjects with ≥3 MetS components ( n = 22) were compared with controls selected from the same cohort at a 1:2 ratio ( n = 44). For each case, the first two patients following those with MetS within the same series who were the same age (±4 years) and who showed a similar TT level (± 4 nmol l −1 ), smoking habit (current/nonsmoker) and moderate-severe alcohol consumption (current/no consumption of ≥4 drinks per day based on a previous publication41). For statistical analyses that compared cases with age-, TT-, smoking habit-, moderate-severe alcohol consumption-matched controls, associations with P < 0.05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristics of this study have been previously reported (18). Lifestyle factors, such as education (18), or smoking (18) and drinking (66) habits, also have deleterious effects on forthcoming MACEs. Information on mortality up to 31 December 2007, including causes of death, was obtained from the City of Florence Registry Office, which contains complete and updated records of all individuals living within city boundaries.…”
Section: Testosterone and Cardiovascular Diseases In Subjects With Sementioning
confidence: 97%